UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER PADA SISWA KELAS XI IIS MAN 2 PASAMAN BARAT - BETRI HARIANI (STKIP Pesisir Selatan, 2019)
Based on student learning outcomes in Class XI IIS MAN 2 Pasaman Barat in mathematics it was found that student learning outcomes in mathematics are still very low. The average student learning outcomes are still below the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in mathematics subject to Geometry Transformation (Translations) through the Numbered Head Together learning model in Class XI IIS MAN 2 Pasaman Barat Pasaman Barat Regency. This research is a classroom action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 36 students of Class XI IIS MAN 2 Pasaman Barat. Research data were collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of research and discussion that has been stated, it can be concluded that the Numbered Head Together learning model can improve student learning outcomes in mathematics sub Geometry Transformation (Translations) in MAN 2 Pasaman Barat. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle was 59.42 (enough) increased to 84.73 (good) with an increase of 25.31%.